Two sides of modernity and its architecture = Dua sisi kemodenan dan senibina - Spahic, Omer (International Islamic University Malaysia, 2019)
This paper discusses the two-sidedness of modernity and its architectural evolution. The paper concludes that modernity was exclusively a Western concept exported to the rest of the world. It was incubated by the weakening and marginalization of Christianity as a worldview and way of life, the rise of capitalism, and the worship-like attitude towards science and technology in everyday life. The world of architecture, especially its modernist school of thought and style, clearly reverberated such developments. Since its inception, modernity recognized no spiritual power or authority. It held inviolable only man and his capacities, plus his rapid scientific and technological progress.